The politic of the culture. The de/colonialism and interculturalism of the national in the Andean America - Miranda Delgado, Rafael Gustavo (2015)
This article seeks to locate in the intertwining of the political and cultural expressions, where their boundaries are blurred in a complex and irreducible reality. It seeks to make evident the relationship between politics and culture, understanding this, from a critical and anthropological perspective as a problematic space, struggles and intentions. For this, we analyze the processes de/colonialism of nation and intericulturalism in the Andean America.